Riwayat Komplikasi Maternal terhadap Insiden Kelahiran Prematur di RSUD Dr. H. Chadan Boesoirie Ternate - Siska Nawang Ayunda Maqfiro; Irmasanti Fajrin (Poltekkes Kemenkes Maluku, 2020)
Premature birth is one of the most important factors in neonatal morbidity and mortality. Based on the survey shows an increase in the incidence of premature birth at dr. H. Chasan Boesoirie hospital in 2015-2017. The purpose of this study was to determine the relationship between the history of maternal complication and the incidence of premature birth at dr. H. Chasan Boesoirie hospital used an analytic correlation research design with a cross-sectional approach. The population is all multiparity and grand multiparity at dr. H. Chasan Boesoirie hospital on January-December 2018, the sampling technique used simple random sampling, with the total sample are 196 respondents. The results show that 66,3% do not have the history of maternal complication and 85,7% do not have an incidence of premature birth. Then, that were analyzed using Spearman-rank. The results show that p-value is 0,001 (p-value<α). The conclusion that there is a relationship between the history of maternal complication and the incidence of premature birth at dr. H. Chasan Boesoirie hospital. So, it is necessary to provide information and education to pregnant women in order to plan their pregnancy well and build a referral system with primary care facilities.